Photocatalytic high-antibacterial polyaryletherketone composite material and preparation method thereof
By loading the inorganic antibacterial sol in porous polyaryletherketone and using photocatalytic effects, the problem of insufficient biological inertia in the medical field of polyaryletherketone is solved, and a composite material with high antibacterial properties and good mechanical properties is achieved, which is suitable for orthopedics, trauma and oral fields.
Patent Information
- Application Number
- CN202411861846.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing polyaryletherketone materials in the medical field are prone to bacterial adhesion and proliferation due to insufficient biological inertia in the medical field, which in turn triggers an inflammatory response, limiting their application in orthopedics and trauma fields.
By loading the inorganic antibacterial agent sol in porous polyaryletherketone, the antibacterial performance is further enhanced by photocatalytic effects, and a composite material with high antibacterial properties and good mechanical properties is prepared.
It realizes uniform dispersion of inorganic nanoparticles, improves the antibacterial and biocompatibility of composite materials, and has good mechanical properties, suitable for orthopedics, trauma and oral fields.
Smart Images

Figure BDA0005193381500000061 
Figure BDA0005193381500000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyaryletherketone modification, and in particular to a photocatalytic highly antibacterial polyaryletherketone composite material and a preparation method thereof. Background Art
[0002] Polyetheretherketone (PEEK) has been widely used in aerospace, automobile, electronics and other fields due to its unique properties. With the development of materials science and biomedical engineering, PEEK, as a high-performance thermoplastic polymer material, has gradually shown great potential in the medical field.
[0003] PEEK has good thermal stability, with a melting point of up to 343°C. It can maintain stable performance in high temperature environments and is suitable for a variety of processing techniques. At the same time, PEEK has excellent chemical stability, is resistant to acid and alkali corrosion, and is not easily attacked by chemicals. In terms of mechanical properties, PEEK has the characteristics of high strength, high modulus, and low wear rate, which enables it to perform well under load and friction environments. In the biomedical field, PEEK's light transmittance, biocompatibility, and chemical resistance make it an ideal implant material. Compared with traditional metal implant components, PEEK has an elastic modulus that is closer to human bones, which can effectively reduce the stress shielding effect and promote bone integration.
[0004] However, the inherent biological inertness of PEEK limits its application in the medical field. Bacteria easily adhere and proliferate on the surface of PEEK materials, leading to inflammatory reactions, which in turn affect the stability of implants. This problem is particularly prominent in the fields of orthopedics and trauma, and has become the main cause of implant failure. To solve this problem, researchers usually melt-blend polyetheretherketone with antibacterial materials such as nano-titanium dioxide and nano-zinc oxide to prepare composite materials. However, nanoparticles are usually easy to agglomerate due to their high specific surface area and small size effect, causing them to be unevenly dispersed in the melt, so that the material performance cannot be effectively exerted. Therefore, how to achieve uniform dispersion of inorganic nano-antibacterial materials in PEEK and ensure long-term stability is still the main challenge facing current research. Summary of the invention
[0005] In order to solve the above technical problems, a photocatalytic highly antibacterial polyaryletherketone composite material and a preparation method thereof are provided. The present invention loads an inorganic antibacterial agent sol into the pores of porous polyaryletherketone, improving the processing performance while making the composite material prepared by subsequent molding have excellent antibacterial properties and good mechanical properties.
[0006] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0007] A method for preparing a photocatalytic highly antibacterial polyaryletherketone composite material comprises the following steps:
[0008] S1. Preparation of porous polyaryletherketone: mixing polyaryletherketone with a solid good solvent, heating until the solid good solvent melts and the polyaryletherketone dissolves, stirring and mixing evenly, cooling at a cooling rate of 0.1-5°C / min to solidify the entire system (polyaryletherketone recrystallizes) to obtain an intermediate, extracting the solid good solvent contained in the intermediate, and drying to obtain porous polyaryletherketone;
[0009] S2, preparation of composite materials: adding the porous polyaryletherketone to the inorganic antibacterial agent sol, mixing by ultrasonic stirring, drying at a drying temperature greater than the glass transition temperature of the porous polyaryletherketone and less than the melting point temperature, and forming after extrusion granulation or directly forming to obtain a photocatalytic high antibacterial polyaryletherketone composite material. Forming processes such as injection molding and compression molding are all possible.
[0010] Furthermore, the porous polyaryletherketone has a pore size of 30-50 nm and a porosity of 80%-90%. Within this range, the specific surface area of the porous polyaryletherketone is 130-170 m 2 / g range, density is 1.3-1.4g / cm 3 The colloidal particle size of the inorganic antimicrobial agent sol is smaller than the pore size of the porous polyaryletherketone, which can ensure the inflow load.
[0011] Furthermore, the solid good solvent is selected from one of diphenyl sulfone and p-phenylphenol.
[0012] Furthermore, the temperature for heating the solid good solvent to melt and dissolve the polyaryletherketone in S1 is in the range of 168° C.-200° C., and the time for stirring and mixing uniformly is in the range of 10 min-60 min.
[0013] Furthermore, the cooling rate in S1 is in the range of 0.5-3°C / min; the temperature at which the entire system is solidified by cooling is 100°C-120°C; the mass percentage of the polyaryletherketone and the solid good solvent is in the range of 10%-30%:70%-90%; and the extraction is performed using anhydrous ethanol or anhydrous methanol for at least 24 hours. The density and porosity of porous polyaryletherketone are controlled by the polyaryletherketone concentration in the system. Increasing the polyaryletherketone concentration leads to increased density and decreased porosity, while high-porosity materials have larger specific surface area and internal space, which is conducive to the stable loading and uniform dispersion of the active ingredients in the subsequent inorganic antimicrobial agent sol. By controlling the cooling rate of the system, the crystallinity of the solute polyaryletherketone in the good solvent can be regulated (low cooling rate allows PEEK to have a longer crystallization time at a temperature above Tg, with a higher crystallinity, forming a more dense and larger PEEK uniform microporous structure, while producing a higher specific surface area; increasing the cooling rate makes the crystallization process occur rapidly, and the crystallinity is relatively reduced). High crystallinity can make the polyaryletherketone molecules stacked tightly, thereby obtaining porous polyaryletherketone with better mechanical properties than sulfonated polyetheretherketone.
[0014] Furthermore, in S2, after drying at a drying temperature greater than the glass transition temperature of the porous polyaryletherketone and less than the melting point temperature, the inorganic antimicrobial agent sol reacts in situ to obtain an inorganic antimicrobial agent. The drying temperature is set according to the glass transition temperature and melting point temperature of the corresponding polyaryletherketone. For example, the glass transition temperature of PEEK is about 143°C and the melting point is about 340-350°C. The drying temperature can be set to 160°C-250°C and the drying time can be at least 12 hours to completely decompose the sol therein to form the corresponding inorganic antimicrobial agent.
[0015] Furthermore, the inorganic antibacterial agent is selected from one or more of nano zinc oxide, nano aluminum oxide, nano silicon dioxide, nano titanium dioxide, nano copper oxide, and nano silver oxide;
[0016] The inorganic antibacterial agent sol is obtained by mixing a solution of one or more of a zinc source, an aluminum source, a silicon source, a titanium source, a copper source, and a silver source with an alkaline solution to obtain a corresponding sol. The zinc source, the aluminum source, the titanium source, the copper source, and the silver source are usually their corresponding sulfates, nitrates, chlorides, etc., and the silicon source is usually silicate. The solution can be pure water or a mixture of water and alcohol.
[0017] Furthermore, the mass fraction of the inorganic antibacterial agent sol is 5%-6%; the mass volume ratio of the porous polyaryletherketone to the inorganic antibacterial agent sol is in the range of 1g / 1.8-3mL.
[0018] Furthermore, the polyaryletherketone is selected from polyetheretherketone (PEEK), polyetherketone (PEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK) and polyetherketoneetherketoneketone (PEKEKK), and has a melt index in the range of 8-10 g / 10 min.
[0019] Furthermore, the inorganic antibacterial agent accounts for 8wt%-10wt% of the photocatalytic high antibacterial polyaryletherketone composite material.
[0020] Another aspect of the present invention provides a photocatalytic and highly antibacterial polyaryletherketone composite material obtained by the above preparation method.
[0021] Beneficial technical effects:
[0022] The present invention prepares a porous polyaryletherketone with a certain pore size and a large porosity through the process of dissolution, coagulation and extraction, and the pores are evenly distributed, and then an inorganic antibacterial agent sol is loaded in the porous body, and a nano inorganic antibacterial agent is generated in situ and loaded in the polyaryletherketone, and then the antibacterial polyaryletherketone is obtained by direct molding or extrusion granulation. The method of the present invention can make the inorganic nanoparticles disperse more evenly in the matrix, so that the composite material has better antibacterial and biocompatibility on the basis of having good mechanical properties, and the antibacterial agent can perform photocatalysis to further play a bactericidal role. The composite material of the present invention is expected to be more widely used in the fields of orthopedics, trauma, dentistry, etc. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0025] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, they are carried out in accordance with general standard requirements or general methods.
[0026] Preparation Example
[0027] Zn(OH) 2 Preparation of sol: At room temperature, 1000 mL of 2.4 mol / L NaOH aqueous solution was added dropwise (dropping rate 20 mL / min) to 1000 mL of 1.23 mol / L ZnSO 4 The aqueous solution was stirred at 800 rpm for 3 hours to form a uniform sol-like particle size of about 20 nm Zn(OH) 2 Sol (5wt%).
[0028] Preparation of zinc-aluminum sol: At room temperature, 1000 mL of 4.2 mol / L NaOH aqueous solution was added dropwise (dropping rate 20 mL / min) to 500 mL of 1.2 mol / L ZnSO 4 aqueous solution and 500mL of 1mol / L Al 2 (SO 4 ) 3 In aqueous solution (ZnSO 4 Aqueous solution and Al 2 (SO 4 ) 3 The aqueous solution was mixed uniformly in advance), and stirred at 800 rpm for 4 hours to form a zinc-aluminum sol (5 wt %) with a uniform sol-like particle size of about 5-30 nm.
[0029] Preparation of zinc-titanium sol: At room temperature, 1000 mL of 1.2 mol / L NaOH aqueous solution was added dropwise (dropping rate 20 mL / min) to 500 mL of 1.24 mol / L ZnSO 4 aqueous solution and 500mL of 10wt% titanium dioxide sol (ZnSO 4 The aqueous solution and the titanium dioxide sol were mixed uniformly in advance), and stirred at 800 rpm for 5 hours to form a zinc-titanium sol (5 wt%) with a uniform sol-like particle size of about 5-20 nm.
[0030] Example 1
[0031] A method for preparing a photocatalytic highly antibacterial polyaryletherketone composite material comprises the following steps:
[0032] S1. Preparation of porous PEEK: 200 g of polyetheretherketone and 800 g of p-phenylphenol powder were mechanically mixed uniformly, heated to 180°C to melt p-phenylphenol to form a liquid good solvent, and then stirred for 20 min to uniformly dissolve PEEK in the liquid good solvent to form a clear solution, then stopped stirring and cooled at a cooling rate of 1°C / min. During the cooling process, the solution gradually became turbid, and the entire system solidified to produce a gel, and further cooled to 120°C to obtain an intermediate; p-phenylphenol was removed by Soxhlet extraction with anhydrous ethanol for 48 hours, and then dried in a vacuum oven at 60°C to constant weight to obtain porous PEEK with a pore size of about 40-50 nm and a porosity of about 85%-88%;
[0033] S2. Preparation of composite materials: 900 g of the porous PEEK was divided into 5 batches and added to the 2000 mL Zn(OH) 2 The sol was mixed with ultrasonic stirring (ultrasonic power 120W, frequency 20-50Hz, stirring rate 800-1000rpm) for 60min, and the nano-sized Zn(OH) was uniformly loaded in the micron pores on the porous PEEK surface by ultrasonic stirring. 2 , and then placed in a vacuum drying oven at 160°C for 72 hours. During the drying process, Zn(OH) 2 The ZnO@PEEK composite material is obtained by high temperature decomposition, and then ground into fine powder, extruded and granulated at 360-380°C, and then injection molded to obtain a photocatalytic and highly antibacterial polyetheretherketone composite material, in which ZnO accounts for 10wt%.
[0034] Example 2
[0035] A method for preparing a photocatalytic highly antibacterial polyaryletherketone composite material comprises the following steps:
[0036] S1. Preparation of porous PEEK: 250 g of polyetheretherketone and 750 g of p-phenylphenol powder were mechanically mixed uniformly, heated to 200°C to melt p-phenylphenol to form a liquid good solvent, and then stirred for 15 min to uniformly dissolve PEEK in the liquid good solvent to form a clear solution, then stopped stirring and cooled at a cooling rate of 0.5°C / min. During the cooling process, the solution gradually became turbid, and the whole system solidified to produce a gel, which was further cooled to 110°C to obtain an intermediate; p-phenylphenol was removed by Soxhlet extraction with anhydrous ethanol for 60 h, and then dried in a vacuum oven at 60°C to constant weight to obtain porous PEEK with a pore size of about 30-40 nm and a porosity of about 85%-88%;
[0037] S2. Preparation of composite materials: A total of 900 g of the porous PEEK was divided into 8 batches and added to the 2000 mL zinc-aluminum sol prepared above, and mixed with ultrasonic stirring (ultrasonic power 110 W, frequency 20-50 Hz, stirring rate 800-1000 rpm) for 60 min. The nanometer pores on the surface of the porous PEEK were evenly loaded with nanometer-scale zinc-aluminum hydroxide by ultrasonic stirring, and then placed in a vacuum drying oven at 220°C for 72 hours. During the drying process, the zinc-aluminum hydroxide was decomposed into aluminum-doped zinc oxide AZO at high temperature to obtain an AZO@PEEK composite material, which was ground into fine powder, extruded and granulated at 360-380°C, and then injection molded to obtain a photocatalytic and highly antibacterial polyetheretherketone composite material, in which AZO accounted for 10wt% (zinc oxide in AZO accounted for 5wt%).
[0038] Example 3
[0039] A method for preparing a photocatalytic highly antibacterial polyaryletherketone composite material comprises the following steps:
[0040] S1. Preparation of porous PEEK: 150 g of polyetheretherketone and 850 g of p-phenylphenol powder were mechanically mixed uniformly, heated to 170°C to melt the p-phenylphenol to form a liquid good solvent, and then stirred for 25 min to uniformly dissolve the PEEK in the liquid good solvent to form a clear solution, then stopped stirring and cooled at a cooling rate of 2°C / min. During the cooling process, the solution gradually became turbid, and the entire system solidified to produce a gel, and further cooled to 120°C to obtain an intermediate; p-phenylphenol was removed by Soxhlet extraction with anhydrous ethanol for 52 hours, and then dried in a vacuum oven at 60°C to constant weight to obtain porous PEEK with a pore size of about 45-50 nm and a porosity of about 85%-88%;
[0041] S2. Preparation of composite materials: 900 g of the porous PEEK was divided into 6 batches and added to the 2000 mL zinc-titanium sol prepared above, and ultrasonically stirred (ultrasonic power 130 W, frequency 20-50 Hz, stirring rate 800-1000 rpm) for 60 min to uniformly load nano-sized Zn(OH) in the micron pores on the surface of the porous PEEK by ultrasonic stirring. 2 The titanium dioxide sol particles were coated and then placed in a vacuum drying oven at 160°C for 72 hours. During the drying process, Zn(OH) 2 The coated titanium dioxide sol particles are decomposed at high temperature into zinc oxide coated titanium dioxide to obtain a zinc oxide coated titanium dioxide@PEEK composite material, which is ground into fine powder, extruded and granulated at 360-380°C and then injection molded to obtain a photocatalytic and highly antibacterial polyetheretherketone composite material, in which the zinc oxide coated titanium dioxide accounts for 10wt% (of which zinc oxide accounts for 5wt%).
[0042] Comparative Example 1
[0043] The composite material of this case is prepared by melt blending and granulating sulfonated polyetheretherketone (sulfonation degree 60-65%) and nano zinc oxide (average particle size 40-50nm) (the operation is the same as that in Example 1) to obtain an antibacterial polyetheretherketone composite material, in which nano zinc oxide accounts for 12wt%.
[0044] Comparative Example 2
[0045] The preparation process of the composite material in this case is the same as that in Example 1, except that: there is no porous PEEK in S1, and S2 uses sulfonated polyetheretherketone (sulfonation degree 65-70%) and Zn(OH) 2 The sols were mixed and the subsequent operations were the same as in Example 1.
[0046] Comparative Example 3
[0047] The preparation process of the composite material in this case is the same as that in Example 1, except that the cooling rate in S1 is 10°C / min.
[0048] Comparative Example 4
[0049] The preparation process of the composite material in this case is the same as that in Example 1, except that: 400 g of polyetheretherketone and 600 g of p-phenylphenol powder are taken in S1.
[0050] Comparative Example 5
[0051] The preparation process of the composite material in this case is the same as that in Example 1, except that: in S2, the porous PEEK prepared in S1 is directly melt-blended, extruded and granulated with nano zinc oxide (the particle size is the same as that in Comparative Example 1), and injection molded (the operation is the same as that in Example 1) to obtain an antibacterial polyetheretherketone composite material, in which nano zinc oxide accounts for 12wt%.
[0052] The performance of the composite materials in the above cases was tested, and the results are shown in Table 1.
[0053] Table 1 Composite material properties of each case
[0054]
[0055]
[0056] As can be seen from Table 1, the porous polyaryletherketone with a certain pore size and a large porosity is prepared by the process of dissolution, coagulation and extraction, and then the nano antibacterial agent is loaded in situ to prepare a composite material. Since the pores on the surface and inside of the porous matrix are evenly distributed, the composite material has a tensile strength greater than 120 MPa and a bending strength greater than 170 MPa. It not only has a high thermal conductivity and good heat transfer performance, but also has high antibacterial properties in the dark and under light.
[0057] Comparative Example 1 uses sulfonated PEEK to directly melt-blend with nano zinc oxide to prepare a composite material, and Comparative Example 2 uses sulfonated polyetheretherketone and Zn(OH) 2 After the sol is mixed to generate nano zinc oxide in situ, it is melt blended to prepare a composite material. Since the two use sulfonated polyetheretherketone, the pore distribution is uniform, and the pores are mostly distributed on the surface of the material, PEEK and nano zinc oxide are blended unevenly, which affects the overall mechanical properties, antibacterial properties, and photocatalytic antibacterial properties of the composite. Comparative Example 3 uses a larger cooling rate, so that the crystallization process of PEEK occurs rapidly during solidification, and the crystallinity is relatively reduced, which affects the mechanical properties of the matrix. Comparative Example 4 increases the solid content of PEEK in the system, which reduces the porosity of the porous material, has an adverse effect on the stable loading and uniform dispersion of the active ingredients in the subsequent inorganic antibacterial agent sol, and its mechanical properties are adversely affected compared with Example 1. Comparative Example 5 does not form nano zinc oxide in situ in porous PEEK. Since the average particle size must contain nano zinc oxide with a larger particle size, it is difficult to load, which leads to an increase in the amount of nano zinc oxide used directly, and the nano zinc oxide in the pores is unevenly loaded. Compared with Example 1, its mechanical properties and antibacterial properties are adversely affected.
[0058] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a photocatalytic highly antibacterial polyaryletherketone composite material, characterized in that: The steps include: S1. Preparation of porous polyaryletherketone: mixing polyaryletherketone with a solid good solvent, heating until the solid good solvent melts and the polyaryletherketone is dissolved, stirring and mixing evenly, cooling at a cooling rate of 0.1-5°C / min to solidify the entire system to obtain an intermediate, extracting the solid good solvent contained in the intermediate, and drying to obtain porous polyaryletherketone; S2. Preparation of composite materials: adding the porous polyaryletherketone to an inorganic antibacterial agent sol, mixing by ultrasonic stirring, drying at a drying temperature greater than the glass transition temperature of the porous polyaryletherketone and less than the melting point, and molding after extrusion granulation or directly molding to obtain a photocatalytic highly antibacterial polyaryletherketone composite material.
2. The method for preparing a photocatalytic and highly antibacterial polyaryletherketone composite material according to claim 1, characterized in that: The porous polyaryletherketone has a pore size of 30-50nm and a porosity of 80%-90%.
3. The method for preparing a photocatalytic and highly antibacterial polyaryletherketone composite material according to claim 2, characterized in that: The solid good solvent is selected from one of diphenyl sulfone and p-phenylphenol.
4. The method for preparing a photocatalytic and highly antibacterial polyaryletherketone composite material according to claim 3, characterized in that: The temperature for heating the solid good solvent to melt and dissolve the polyaryletherketone in S1 is in the range of 168° C. to 200° C., and the time for stirring and mixing to be uniform is in the range of 10 min to 60 min.
5. The method for preparing a photocatalytic and highly antibacterial polyaryletherketone composite material according to claim 3, characterized in that: The cooling rate in S1 is in the range of 0.5-3°C / min; the temperature at which the entire system is solidified by cooling is 100°C-120°C; the mass percentage of the polyaryletherketone and the solid good solvent is in the range of 10%-30%:70%-90%.
6. The method for preparing a photocatalytic and highly antibacterial polyaryletherketone composite material according to claim 3, characterized in that: In S2, after drying at a drying temperature greater than the glass transition temperature and less than the melting point of the porous polyaryletherketone, the inorganic antibacterial agent sol is reacted in situ to obtain an inorganic antibacterial agent.
7. The method for preparing a photocatalytic and highly antibacterial polyaryletherketone composite material according to claim 6, characterized in that: The inorganic antibacterial agent is selected from one or more of nano zinc oxide, nano aluminum oxide, nano silicon dioxide, nano titanium dioxide, nano copper oxide, and nano silver oxide; The inorganic antibacterial agent sol is obtained by mixing one solution or multiple composite solutions of zinc source, aluminum source, silicon source, titanium source, copper source and silver source with an alkaline solution to obtain the corresponding sol.
8. The method for preparing a photocatalytic and highly antibacterial polyaryletherketone composite material according to claim 6, characterized in that: The mass fraction of the inorganic antibacterial agent sol is 5%-6%; the mass volume ratio of the porous polyaryletherketone to the inorganic antibacterial agent sol is in the range of 1g / 1.8-3mL.
9. The method for preparing a photocatalytic and highly antibacterial polyaryletherketone composite material according to claim 6, characterized in that: The polyaryletherketone is selected from polyetheretherketone, polyetherketone, polyetherketoneketone, polyetheretherketoneketone and polyetherketoneetherketoneketone, and has a melt index in the range of 8-10 g / 10 min.
10. The photocatalytic and highly antibacterial polyaryletherketone composite material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The inorganic antibacterial agent accounts for 8wt%-10wt% in the photocatalytic high antibacterial polyaryletherketone composite material.
Citation Information
Patent Citations
Porous polyaryletherketone material with bioactivity, and preparation method and application thereof
CN105233335A
Porous moulded body and manufacturing method thereof
CN110669338A
Long-acting renewable antibacterial polyether-ether-ketone as well as preparation method and application thereof
CN114316355A
Preparation method of light degradation resistant inorganic fiber / polyaryletherketone composite material
CN118562276A
Antibacterial polyether-ether-ketone microspheres and preparation method thereof
CN118834411A